Investigations into traditionally managed Djallonke-sheep production in the humid and subhmid zones of Asante, Ghana. I. The natural conditions and the agricultural resources of the area - London, C.J.; Weniger, J.H. (Wiley, 1994)
Studies 42 household units in two ecological zones of four farming villages located in the heart of Kumawu Traditional Area (KTA) in Asante, Ghana. The traditional area is the largest (9,256 sq. km) of the 21 traditional areas or paramouncies comprising the Kumawu, which is located 56 km north-east of Kumase, the capital of Asante region. Descriptions of physical conditions, the land tenure system and the current agricultural resources of the area are given. Discusses the physical characteristics of sheep type, ownership pattern and management practices, as well as flock structure. The availabilty of fodder plants and their seasonal cover outlined. In all, the studies covered 700 dams with almost 1500 lambings over a period of 30 months.